Transforming Novosibirsk into the capital of Siberia in the early 1920s - S. A. Papkov (Омский научный вестник: Серия "Общество. История. Современность")
The development of Novonikolaevsk (Novosibirsk) and its transformation into a city of all-Siberian importance is connected with the construction of the Trans-Siberian Railway and the growth of the city’s economy due to its favorable geographical location. The decision about Novonikolayevsk as a residence of Siberia’s governing bodies was made in a hurry, with the resistance of various interested parties and was finally approved in the spring of 1921 in the conditions of acute crisis caused by the consequences of the civil war. In such an environment the mass transfer from Omsk and the organization of all-Siberian institutions in Novonikolaevsk began, with the simultaneous creation of provincial government bodies in the city as well. As a result, this led to enormous problems with the accommodation of numerous employees with their families and strenuous efforts to overcome the housing crisis. Radical measures were taken to solve the difficulties: emergency commissions were set up to search for and distribute premises, mass evictions outside the city of residents not connected with service in Soviet institutions were carried out. But these measures had only a minor effect — the housing crisis and the shortage of office space persisted for decades.